Analisa Kuat Tekan dan Kuat Tarik Beton dengan Menggunakan Batu Apung Sebagai Substitusi Agregat Halus - Firdaus Rizal Auliya Hadi; Ditya Ikram Rif’aa; Pratikso Pratikso (Journal of Engineering and Applied Technology, 2026)
This study aims to analyze the effect of using pumice as a partial substitute for fine aggregate on the compressive strength, splitting tensile strength, flexural strength, unit weight, and workability of lightweight concrete. The research method employed laboratory experiments with a design strength of fc’ 20 MPa based on SNI 7656:2012. The pumice substitution levels were set at 0%, 5%, 10%, and 15% of the fine aggregate weight, with the addition of a superplasticizer at 0.5% of the cement weight. Tests were conducted at 7 and 28 days of concrete age using a Universal Testing Machine to obtain the concrete’s mechanical parameters. The results showed that increasing the pumice content caused a decrease in the concrete’s unit weight and slump value due to the high porosity and water absorption of the pumice aggregate. Substitution levels of 5% and 10% still produced relatively stable compressive strength, tensile strength, and flexural strength, meeting the design quality standards for normal concrete. A 15% substitution showed a more significant decrease in mechanical strength due to increased internal voids and weak interlocking between materials. This study confirms that pumice has the potential to be used as an alternative material in the development of lightweight concrete with controlled weight efficiency and mechanical performance.